2006
DOI: 10.1159/000095987
|View full text |Cite
|
Sign up to set email alerts
|

Adipose Tissue Engineering by Human Adipose-Derived Stromal Cells

Abstract: Tissue engineering has emerged as a promising alternative approach to current clinical treatments for restoration of soft tissue defects. The purpose of this study was to investigate adipose tissue formation in vitro and in vivo by using human adipose-derived stromal cells (ADSCs) utilizing a gelatin sponge (Gelform®) as a scaffold. Adipogenic potentials of human ADSCs were demonstrated by Oil-O-red staining and cellular morphology. After seeding human ADSCs in a density of 3 × 106 cells/ml on three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
71
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(74 citation statements)
references
References 45 publications
2
71
0
1
Order By: Relevance
“…6 and Fig. 7), as reported previously by others [14,16,18,20,32]. We used the huADSC generated from the fat tissue of a 65-year-old donor to treat ICH inflicted rats and evaluated functional behavior of the rats for 28 days.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…6 and Fig. 7), as reported previously by others [14,16,18,20,32]. We used the huADSC generated from the fat tissue of a 65-year-old donor to treat ICH inflicted rats and evaluated functional behavior of the rats for 28 days.…”
Section: Discussionmentioning
confidence: 94%
“…Many studies have indicated that human adipose-derived adult stem cells are a population of mesenchymal stem cells and demonstrated differentiation of stem cells into adipocytes, chondrocytes, myocytes, osteoblasts and neural progenitor cells after chemical inductions [14,16,18,20,32]. Transplantation of matured adipocyte-derived cells and dedifferentiated fat cells to promote functional recovery from spinal cord injury-induced motor dysfunction in rats was reported [20] and an attempt of cellular therapy employing human adipose tissue-derived stromal cells for rats with cerebral ischemia after MCAO resulted in significant functional improvement [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, a thorough digestion and disperse is required to obtain purified adipocytes. Fat tissue has complex cellular composition, including adipocytes, ASCs, preadipocyte, fibroblasts, blood cells, endothelial cells, pericytes, smooth muscle cells and so on [3,9,25,[27][28][29][30][31][32]. The purity of derived DFAT cells might be compromised by the contamination of those cells above when they're attached to the floating adipocytes after incomplete enzymatic treatment.…”
Section: Establishment Of Dfat Cellsmentioning
confidence: 99%
“…ADSCs can also be induced to produce mineralized substrates when cultured under osteogenic conditions in vitro (Leong et al, 2008). It has also been shown that human ADSCs inoculated into mice with severe combined immunodeficiency could form bones in vivo (Hong et al, 2006). Lentiviruses, which are based on the human immunodeficiency virus, have been used as delivery systems to insert genetic information into the DNA of host cells.…”
Section: Introductionmentioning
confidence: 99%